Complexities and Dynamics of the Popular Movement of 1990 in Nepal - Bhandari, Arjun Bahadur (Trunojoyo University of Madura, 2024)
After decades of autocratic control, Nepal's political landscape saw a dramatic change in 1990 when the democratic revolution brought multiparty democracy back. This article examines the tactics, difficulties, and final success of political parties in launching and maintaining the movement. Utilizing historical narratives, primary materials, and academic examinations, it offers perspectives on how political parties evolved into catalysts for transformation, galvanized the populace, and engaged in negotiations with the king to usher in a novel phase of democracy in Nepal. The complex dynamics influenced by many social, political, and economic elements led to the movement's success. In the face of authoritarianism and popular discontent, the study explores the intricacies of the movement and sheds insight on the interlocking dynamics that drove Nepal toward democratic reform